2011
DOI: 10.1002/pro.762
|View full text |Cite
|
Sign up to set email alerts
|

A conserved interaction with the chromophore of fluorescent proteins

Abstract: The chromophore of fluorescent proteins, including the green fluorescent protein (GFP), contains a highly conjugated imidazolidinone ring. In many fluorescent proteins, the carbonyl group of the imidazolidinone ring engages in a hydrogen bond with the side chain of an arginine residue. Prior studies have indicated that such an electrophilic carbonyl group in a protein often accepts electron density from a main-chain oxygen. A survey of high-resolution structures of fluorescent proteins indicates that electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
4
7
0
Order By: Relevance
“…The results from the calculations indicate that the H-O···C=O interaction has a significant role in stabilizing the excited state via an n (OH) →π* (CO) interaction, which results in a low-lying LUMO state and a red-shifted fluorescence. The results are consistent with those reported by Raines and co-workers30, in which theoretical calculations and high-resolution structures of green fluorescent proteins revealed the existence of a n→π* interaction between the chromophore of fluorescent proteins and a main-chain oxygen, and this interaction could contribute to the photophysical properties of the chromophore. Based on the above-mentioned results, the EDF behaviour can be explained by the electronically excited state manifold of the carbonyl groups due to the oscillating HO···C=O interactions caused by the collective proton motion system.…”
Section: Resultssupporting
confidence: 92%
“…The results from the calculations indicate that the H-O···C=O interaction has a significant role in stabilizing the excited state via an n (OH) →π* (CO) interaction, which results in a low-lying LUMO state and a red-shifted fluorescence. The results are consistent with those reported by Raines and co-workers30, in which theoretical calculations and high-resolution structures of green fluorescent proteins revealed the existence of a n→π* interaction between the chromophore of fluorescent proteins and a main-chain oxygen, and this interaction could contribute to the photophysical properties of the chromophore. Based on the above-mentioned results, the EDF behaviour can be explained by the electronically excited state manifold of the carbonyl groups due to the oscillating HO···C=O interactions caused by the collective proton motion system.…”
Section: Resultssupporting
confidence: 92%
“…In natural fluorescent proteins, such as green fluorescent protein (GFP), an n →π* interaction forms between a backbone oxygen and the imidazolidine chromophore ( 14 ). 92 The presence of this n →π* interaction is consistent with the red shift in the vibrational frequency of the imidazolidine carbonyl group in the protein-bound chromophore relative to small-molecule mimics in solution. Moreover, analyses of protein crystal structures with premature chromophores suggest that this n →π* interaction preorganizes the chromophore for cyclization and precludes bond rotations that would lower the quantum yield.…”
Section: Contributions To Small Moleculessupporting
confidence: 52%
“…An additional interaction between the C 2 atom and the carbonyl O atom of Thr62 can be regarded as a lone pair-* interaction [Figs. 8(b) and 8(c)] (Choudhary et al, 2012), which actually weakens the C 2 -O 2 bond, as indicated from the bond order shown in Supplementary Fig. S5(c).…”
Section: Nonbonded Interactions Around the Chromophorementioning
confidence: 83%